DINAMIKA PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DALAM KELAS: STUDI DI SMA N 6 BENGKULU TENGAH - Ni'am, Falahun; Ramea Astri, Tita; Amaliah, Riski; Dwi Setia Anugrah, Muhamad Fadli; Ilham, Ahmad (Jurnal Ilmu Pendidikan Islam, 2025)
The development of information and communication technology has driven transformation in the world of education, including digitalization in learning. This research explores the application of digital learning media at SMA N 6 Central Bengkulu, its impact on students, and the challenges in its implementation. The method used is descriptive qualitative with data collection techniques through observation, interviews and document analysis. The research results show that the use of digital media, such as PowerPoint, learning videos and online platforms, can increase student motivation and understanding. However, there are challenges such as limited infrastructure, lack of teacher training, and student distraction in using technology. To optimize digital learning, strategies are needed that include increasing teacher skills in technology, strengthening school infrastructure, and implementing interactive learning methods. With the right approach, digital media can increase the effectiveness of the teaching and learning process and prepare students to face the digital era.